Mitigating GHG Emissions from Military Supply Chain by Use of Aerial Cable Way - Bhave, Prashant P.; Dhawad, Chetan; Jain, Vibha (Defence Science Journal, 2024)
The transportation sector being one of the significant contributors to greenhouse gas (GHG) emission, there is growing concerns about environmental sustainability, and reducing GHG emissions which has prompted re-evaluation of transportation systems. The 1.5 million strong Indian defence forces have huge transport fleet and this study delves into the potential of Aerial Cableway (ACW) as a promising alternative mode of transport that can significantly reduce emissions of military supply chain in mountainous terrain. The study takes a case of Himalayan terrain to investigate how ACWs offer a low-impact, energy-efficient, and environmentally friendly solution compared to conventional ground-based transportation. It takes a case of Pharkian Pass in North Kashmir where defence forces has presence and this pass is often exposed to frequent landslides, snowfall and avalanches. Every year, on an average, approximately 12,000 trucks cross Pharkian pass in a year for purpose of logistics and sustenance. Without touching sensitive issues and by using a multi-criteria-based cost-benefit analysis, the study establishes that even if 75 % of road transport trips are shifted to ACWs, the reduction of GHG emissions is by 57.7 % in addition to significant benefits of the social cost of carbon, environmental costs, economic savings and ensuring strategic advantage like all-weather connectivity.